ANALISIS ALTERNATIF REPLACEMENT ATAU LEMBUR PADA PT. MITRATANI DUA TUJUH JEMBER - Subhan Hariadi; Karim Budiono (RELASI : JURNAL EKONOMI, 2012)
PT Mitratani Dua Tujuh in Jember produces soy Edamame for the export market to Japan . Demand from Japan is increasing because Edamame manufacturers from China and Taiwan can not meet the demand from Japan. Increased demand at PT . Mitratani Dua Tujuh can still be met because of agricultural land in Jember still wide enough to produce Edamame. Increasing demand impact on labor requirements , so the company has two (2) alternatives to the use of labor. First, buy a new machine for sorting tool is the Individual Quick Frozen (IQF) or Second , using overtime system using human power . The purpose of the study in order to maximize profits. The analysis used analysis of financial loss (gain ), Net Present Value (NPV) , Internal Rate of Return (IRR) . From the analysis it is known that the largest net profit obtained by alternative purchase a new machine , but when viewed from a NPV analysis using alternative overtime it has a higher NPV . It was concluded that the use of overtime work better when compared to the purchase of a new machine .